Protective effect of pregabalin on the brain tissue of diabetic rats - Demir, Caner F.; Balduz, Metin; Tasci, Irem; Kuloglu, Tuncay (Springer Japan Kk, 2021)
Purpose Diabetes mellitus (DM) is a metabolic disorder characterized by insulin deficiency or insulin resistance. Pregabalin (PGB) is an antiepileptic drug with proven efficacy in the treatment of epilepsy, generalized anxiety disorder, and neuropathic pain. In this study, we aimed to investigate the protective effects of PGB in brain tissue of rats with streptozotocin (STZ)-induced experimental diabetes. Materials and methods Twenty-eight Wistar albino male rats were randomly divided into four groups with seven rats each: (I) Control group, (II) PGB (50 mg/kg PBG), (III) DM, and (IV) DM + PGB (50 mg/kg/day PGB per orally for 8 weeks). Diabetes was induced with an intraperitoneal (i.p.) STZ injection (Sigma Chemical Co Louis Missour, USA) at a dose of 180 mg/kg. STZ was dissolved in 0.1 M phosphate-citrate tampon (pH 4.5). Paraffin sections were examined using histological and immunohistochemical analyses. To detect oxidative damage biochemically, malondialdehyde (MDA), the end product of lipid peroxidation; superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and glutathione peroxidase (GPx) which are antioxidant enzymes, levels were studied. In addition, bax, caspase-3 enzyme activities and TUNEL assay were studied to evaluate the apoptosis status. Results In the DM group, MDA concentrations were significantly higher and GPx and SOD activities were significantly lower compared to the control group. MDA concentrations were significantly lower and SOD activity was significantly higher in the DM + PGB group than in the DM group. The GPx activity in the DM group decreased significantly compared to the control group. In immunohistochemical examinations (Bax, Caspase-3 and TUNEL), the apoptosis rate was significantly lower in the in DM + PGB group than in the DM group. Conclusion Pregabalin may prevent harmful effects of oxidative damage by decreasing the MDA levels and increasing the SOD levels. In addition, it was thought that PGB may have antiapoptotic properties due to decreased bax and caspase-3 immunoreactivity and TUNEL positivity in PGB groups. Based on these findings, we think that PGB may be effective in reducing the risk of brain damage associated with DM.
Keywords: Diabetes mellitus; Pregabalin; Brain; Apoptosis; Oxidative stress